Rural landscape characters for tourism route planning - Zakariya, Khalilah; Ibrahim, Putri Haryati; Ibrahim, Illyani; Che Haron, Roziha; Tukiman, Izawati (2021)
The "Rural Landscape Characters for Tourism Route Planning Framework" was established as a guide to identify significant landscape characters in the rural areas that contribute to the planning of tourism routes. The framework consists of seven criteria, which are 'landscape features and nature'. 'agriculture', 'built environment', 'activities and sense', history and heritage', 'accessibility', and 'tourism infrastructure'.